Up in flames: the human factor behind a megafire in Mediterranean Türkiye - Bikem Ekberzade; Tolga Görüm; Furkan Karabacak; Semih Sami Akay; Ömer Lütfi Şen (npj Natural Hazards)
Abstract On the evening of July 28, 2021, the largest wildfire for the last century broke out in four different locations in a Mediterranean catchment in southern Türkiye; arson cases which came on the heels of anomalous temperatures and precipitation patterns. Aided by strong foehn winds and complex terrain, the Manavgat Fire soon got out of control, spreading to 60,000 ha of dry conifer forest, shrubland, and rural settlements, killing 8 people, burning villages and livestock before it was contained 2 weeks later. In this study, we used climate, meteorology and remote sensing datasets, national fire archives, newspaper articles, dynamic vegetation modelling, site visits to better understand the natural and anthropogenic dynamics behind the wildfire and their impact. Our results highlight the contribution of deliberate human ignitions to the size of the burned area and suggest that effective policy measures can help to avert similar, if not more severe, future incidents.